Derepression of specific miRNA-target genes in rice using CRISPR/Cas9. (20th July 2021) - Lin, Yarong; Zhu, Yiwang; Cui, Yuchao; Chen, Rui; Chen, Zaijie; Li, Gang; Fan, Meiying; Chen, Jianmin; Li, Yan; Guo, Xinrui; Zheng, Xijun; Chen, Liang; et al.
Abstract : CRISPR/Cas9 is used as a strategy to achieve derepression of miRNA-target genes to create elite traits in rice. Abstract: MicroRNAs (miRNAs) target specific mRNA molecules based on sequence complementarity for their degradation or repression of translation, thereby regulating various developmental and physiological processes in eukaryotic organisms. Expressing the target mimicry (MIM) and short tandem target mimicry (STTM) can block endogenous activity of mature miRNAs and eliminate the inhibition of their target genes, resulting in phenotypic changes due to higher expression of the target genes. Here, we report a strategy to achieve derepression of interested miRNA-target genes through CRISPR/Cas9-based generation of in-frame mutants within the miRNA-complementary sequence of the target gene. We show that two rice genes, OsGRF4 ( GROWTH REGULATING FACTOR 4) and OsGRF8 carrying in-frame mutants with disruption of the miR396 recognition sites, escape from miR396-mediated post-transcriptional silencing, resulting in enlarged grain size and increase in brown planthopper (BPH) resistance, in their respective transgenic rice lines. These results demonstrate that CRISPR/Cas9-mediated disruption of miRNA target sites can be effectively employed to precisely derepress particular target genes of functional importance for trait improvement in plants.